2017
DOI: 10.1016/j.desal.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Metallic anion recovery from aqueous streams and removal agent recycle in the polymer–surfactant aggregate process

Abstract: In a previous contribution, a new application of the polymersurfactant aggregate (PSA) process was developed; the removal of metallic anions from dilute aqueous solutions. A subsequent pH adjustment method has been developed to recover the metallic anions from the flocculated PSAs into a concentrated solution and then to recover the polymer (PAA) and surfactant (MTAB) for recycling. A base solution is firstly added to the flocs to leach out the bound metallic anions in 15 minutes, and then a coarse filter is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Further research found adjustment of pH can result in greater recover the metallic anions from the flocculated PSAs into a concentrated solution, essentially recovering the polymer and surfactant for re-use. Results on the overall recycle process have shown that up to 94% of both CrO 4 2− and the PAA-MTAB were recovered and were able to be reused, respectively, upon addition of NaOH and H 2 SO 4 at optimal dosages [125].…”
Section: Surfactant-polymer Aggregate Enhanced Membrane Separationmentioning
confidence: 99%
“…Further research found adjustment of pH can result in greater recover the metallic anions from the flocculated PSAs into a concentrated solution, essentially recovering the polymer and surfactant for re-use. Results on the overall recycle process have shown that up to 94% of both CrO 4 2− and the PAA-MTAB were recovered and were able to be reused, respectively, upon addition of NaOH and H 2 SO 4 at optimal dosages [125].…”
Section: Surfactant-polymer Aggregate Enhanced Membrane Separationmentioning
confidence: 99%
“…In addition, using a cationic surfactant with a longer tail group facilitates the formation of PSAs and the removal of metallic anions [18]. Research results on the overall recycle process have shown that up to 94% of both CrO4 2− and the PAA-MTAB can be recovered and reused, respectively, via addition of NaOH and H2SO4 at the optimum dosage [19].…”
Section: Introductionmentioning
confidence: 99%